2019
DOI: 10.1063/1.5045632
|View full text |Cite
|
Sign up to set email alerts
|

High performance and high power circularly polarized horn antenna for K-band microwave processing systems

Abstract: A single-ridged K-band circularly polarized horn antenna offering excellent performance has been developed by improving the polarization conversion and manufacturing complexity. The numerical and experimental results are consistent showing the return loss of this antenna to be less than −20 dB and the axial ratio at the boresight direction to be less than 0.7 dB in the frequency range from 23.5 GHz to 24.5 GHz. In addition, the gain of this antenna is higher than 20 dB. The newly designed circularly polarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the previous research results [4], it is found that the single ridge structure has a very good effect on narrow frequency applications. In the proposed design, double ridge structure is used since the single ridge structure cannot meet the design conditions at both the low-frequency band (26.5-30.0 GHz) and the high-frequency band (36.0-40.0 GHz).…”
Section: Circularly Polarized Convertermentioning
confidence: 90%
See 2 more Smart Citations
“…In the previous research results [4], it is found that the single ridge structure has a very good effect on narrow frequency applications. In the proposed design, double ridge structure is used since the single ridge structure cannot meet the design conditions at both the low-frequency band (26.5-30.0 GHz) and the high-frequency band (36.0-40.0 GHz).…”
Section: Circularly Polarized Convertermentioning
confidence: 90%
“…Circular polarization antennas are also used in general communication systems to reduce polarization mismatch, increase signal coverage, and inhibit multipath errors [1]. The grooved waveguide, iris-loaded waveguide, septum polarizer, and ridge circular waveguide are the main design structures of circularly polarized antennas [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing researches of polarizers mainly focus on the improvement of bandwidth and miniature design. The representative polarizers consist of metal screws [3], metal irises [4], metal stepped septum [5,6], or dielectric-slab [7], which are placed into waveguide to differentiate the phase of the two orthogonally polarized components. These polarizers meet the demands of polarization conversion experiments and applications.…”
Section: Introductionmentioning
confidence: 99%
“…These polarizers meet the demands of polarization conversion experiments and applications. However, they could not meet the gigawatt-class high-power microwave applications for the tiny-size inserted abrupt structures [3][4][5][6], tending to cause local electric field concentration. Moreover, dielectric-slab polarizer [7] inevitably introduces triple junction, which is prone to result in RF breakdown.…”
Section: Introductionmentioning
confidence: 99%